Factors affecting homework completion among students - Watkins, Lisa (My University, 2012)
This study explored factors affecting student homework completion - individual skills of language, math, and reasoning along with motivation, quality of the assignment, teacher feedback, and the environment in which homework is completed. Ninth grade students at Hudson High School were surveyed to identify which factors were the most prevalent in why students did not complete homework. In addition to the survey, during one unit of the semester, students received "adjusted assignments", that is, shorter, more streamlined homework assignments as well as more classroom time to work individually or with other students in order to see if this type of working environment and assignments led to a higher percentage of students completing homework. The results from the unit in which students received adjusted assignments and more class time to work saw two of the four classes increase in the amount of homework turned in. Three of the four classes showed an increase in the class test GPA when they worked on the adjusted assignments and the fourth class' test GPA remained the same. In a survey of student perceptions about homework factors, students disagreed that the factors which focused on skills (language, reasoning, and math), are reasons as to why they do not complete homework. The other four factors that were surveyed were feedback, environment, motivation, and quality of assignment. Students indicated that they did recognize the purpose and benefits of homework and acknowledged they had motivation to complete homework. Survey results show that students feel as though they work better by themselves or with others as long as the work is done during class time and that they do not receive as much written feedback as they would like regarding their mistakes. Finally, students indicated that they would like choices in assignments as well as opportunities for project-based homework.
Plan B Paper. 2012. Master of Science in Education- Physics--University of Wisconsin-River Falls. Physics Department. 43 leaves. Includes bibliographical references (leaves 27-28).
Keywords: Homework; Academic achievement; Motivation in education; High school students--Attitudes; Study skills; Chemistry--Study and teaching (Secondary)